IDIOPATHIC GASTRIC SUBSEROSAL HEMATOMA – A CASE REPORT - DR.SASIKUMAR PATTABI,; DR.G.K.SHREEDHAR,; DR.S.JAYAKANTHAN,; DR.JAMPANASIVA.S.RAJU., (International Journal of Pharma and Bio Sciences, 2014)
Subserosal hematoma of the gastrointestinal tract is an uncommon occurrence.Hematoma of the gastric wall is very rare, and has been described most commonly in association with coagulopathy, peptic ulcer disease, trauma, and amyloidassociated microaneurysms. A case of gastric subserosal hematoma, secondary to idiopathic cause, requiring surgical intervention is presented.